Simulation of acoustic energy harvester using helmholtz resonator with piezoelectric backplate - Atrah A.B.; Salleh H. (International Institute of Acoustics and Vibrations, 2023)
An acoustic energy harvester using piezoelectric backplate has been studied numerically using COMSOL Multiphysics 4.3. There are many research activities focusing on harvesting various environmental energies. However, acoustic energy harvesting has seldom been studied. In this study, a Helmholtz Resonator is used to collect travelling acoustic waves at frequencies of 3500 to 4500Hz. Piezoelectric ring made of Lead Zirconate Titanate (PZT) is connected with silicone membrane. At the resonance of the Helmholtz Resonator, amplified resonant acoustic standing waves are developed inside the cavity. The pressure difference between the walls drive the vibration motion of the membrane backplate and that leads to generate an electrical power via the direct piezoelectric effect. In COMSOL, the 2D Acoustic-Piezoelectric physics has been used for a frequency domain analysis. Background acoustic pressure is used to simulate an incident plane wave which acoustically excites the membrane. The material properties are also included in simulations to consider sound leakage through resonator walls. The resonance behaviour of the Helmholtz Resonator with the piezoelectric backplate has been studied. The neck radius has been swept with 1 urn interval to investigate the output voltage. When using a parameter sweep for neck length from 50 ?m to 150 ?m, it was found that at 3.5 kHz maximum output voltage was 1.3 mV. In conclusion, the numerical studies of acoustic resonance behaviour of the Helmholtz Resonator with piezoelectric backplate are performed using COMSOL Multiphysics. The harvested voltage and power have been calculated and compared to previous works.